A survey on the information needs of the Ramon Magsaysay (Cubao) High School students towards a proposed information literacy program for the library - Pavo, Dawn Daniel Christine M.; Ramos, Marian S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
Possessing the skills to navigate through the vast information sources available today, or simply being information literate, is necessary to cope in the Information Age. School libraries play a vital role in honing the students to become information literate, thus, integration of information literacy programs offered by the school is deemed important.
This study proposed an information literacy program for the library that aims to address the information needs of the students. A total of 373 students coming from all year levels were surveyed. The data gathered from the questionnaires revealed that: (a) the skill level or knowledge of the students on basic library skills is average; (b) among the resources available in the library, dictionaries (89.10 ), encyclopedias (81.77) and textbooks (81.23) were the most widely used; (c) Philippine history, chemistry and biology turned out to be the subjects where information is mostly used; (c) Philippine history, chemistry and biology turned out to be the subjects where information is mostly used; and (d) students learn more from reading textual information and from conversing with a person.
Recommendations for the study included an additional assessment on how the student processes and searches for information, inclusion of the teaching faculty in the survey, and regular assessment of the needs of students.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information literacy -- Philippines -- Quezon City (Cubao).; High schoo students -- Philippines -- Quezon City (Cubao).